2022
DOI: 10.1155/2022/8955326
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Dance Action Recognition Model Using Deep Learning Network in Streaming Media Environment

Abstract: Dance movement recognition is a video technology that has a significant impact on intelligent applications and is widely applied in many industries. In the training of intelligent dance assistants, this method can be used. Dancers’ postures can be reconstructed by taking the features out of their images. Examine and correct dancers’ postures in order to recognise their dance movements. The most crucial aspect of this technology is effectively extracting features, and deep learning is currently one of the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The Real Temporally Coherent (RTC) model is a deep learning-based action generation model for creating coherent dance movements. The model uses an Encoder-Decoder-like architecture, similar to the architecture used in natural language processing [10]. The encoder consists of a series of convolutional layers that take in the input motion capture data and generate an embedding vector that people the characteristics of the dance movement.…”
Section: Introductionmentioning
confidence: 99%
“…The Real Temporally Coherent (RTC) model is a deep learning-based action generation model for creating coherent dance movements. The model uses an Encoder-Decoder-like architecture, similar to the architecture used in natural language processing [10]. The encoder consists of a series of convolutional layers that take in the input motion capture data and generate an embedding vector that people the characteristics of the dance movement.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%